Stance and Engagement Markers in The Jakarta Post's Opinion Articles (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
A number of research has currently established that written texts represent interactions between writers and readers. A range of linguistic features have been identified as a contribution to the author’s projection of a stance to the material referenced by the text, and, to further extent, the strategies used to presuppose the active role of an addressee. Based on the investigation of ten (10) English written opinion articles published by The Jakarta Post, this study used a qualitative case study approach. This study attempted to address the stance and engagement markers used in the opinion-ed writers page written in English using stance and engagement theory proposed by Hyland (2005) as its framework. This model shows a comprehensive and integrated way of analyzing the means by which interaction is achieved in opinion argument and how the discoursal preferences of disciplinary communities’ construct both writers and readers. Findings show that the interaction is adequately appropriate. The use of stance markers and engagement markers is not necessarily balanced. The study found that the stance markers is used more often than the engagement markers. The writers could have been used more innovatively. The overall findings of the study have both pedagogical and future research implications.